A review of novel methods and current developments of phase change materials in the building walls for cooling applications. (February 2022) - Mukram, T. Anfas; Daniel, Joseph
Highlights: PCM applications in building walls for cooling and related research in current time are reviewed. The thermal comfort enhancement and peak temperature reduction in buildings are discussed. Different natural and commercial PCMs and their usage in building cooling are deliberated. PCM incorporation methods in buildings with associated problems and possible solutions are discussed. Wall applications of PCM as a layer, with cement, and insertion in brick holes are described in detail. Abstract: The prime concern of the scientific community nowadays is high energy consumption and related greenhouse gas (GHG) emission. One of the major energy consumers is building sector, where nearly 30% of total energy is disbursed, with high priority to space cooling and ventilation. In addition, the contribution of buildings for GHG emission is also high. Various researchers in the recent past have suggested and successfully implemented different cooling methods to address this crisis. This paper evaluates various models suggested by researchers for building cooling with phase change materials (PCMs). Since the exposed area of high-rise buildings is more, there is a great chance for energy savings. The PCM impregnated building wall and building brick models have the promising potential for energy saving, by providing thermal comfort and conceding the peak temperature. This article emphasises the wall and building brick applications of PCM for building cooling, that illuminate the associated difficulties and possible alternatives. From the study, it was found that the PCM walls can be constructed with different techniques like adding PCM as a separate layer or inserting PCM in brick holes. In some cases, the PCM is added as a constituent in the cement mortar for plastering or for making concrete. These techniques will help to reduce the building cooling load, peak heat flux, and shift the peak temperature to off working hours. In cooling applications, it is preferred to keep the PCM layer near the heat source for better performance. The performance of a PCM wall highly depends upon the type of PCM used, location of PCM in the wall, type of application, and on the phase transition temperature of PCM.